2016
DOI: 10.1007/s13277-016-5345-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a CD4+CD25−FoxP3+ T cells subset in tumor-draining lymph nodes of colorectal cancer secreting IL-2 and IFN-γ

Abstract: CD4CD25FoxP3 cells are a newly recognized subset of T cells which was first reported in autoimmune diseases. In our previous study, this subset was detected in tumor-draining lymph nodes (TDLNs) of patients with breast cancer. As little is known about their function in TDLNs of cancer patients, in this study, their frequency as well as their ability to produce interleukin (IL)-2, IL-10, or interferon (IFN)-γ were investigated in TDLNs of colorectal cancer (CRC) patients. Mononuclear cells were isolated from ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…CD25 ¡ FoxP3 C cells in CRC patients showed lower suppressive and higher effector properties in comparison to the CD4 C CD25 C FoxP3 C nTregs. 41 Moreover, evidence accumulates that IL-10, produced by these CD25 ¡ Tregs, plays a pivotal role in preventing inflammation and hereditary colon cancer. 38 Instead, nTregs, isolated from PBMC of CRC patients, were capable of inhibiting anti-tumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…CD25 ¡ FoxP3 C cells in CRC patients showed lower suppressive and higher effector properties in comparison to the CD4 C CD25 C FoxP3 C nTregs. 41 Moreover, evidence accumulates that IL-10, produced by these CD25 ¡ Tregs, plays a pivotal role in preventing inflammation and hereditary colon cancer. 38 Instead, nTregs, isolated from PBMC of CRC patients, were capable of inhibiting anti-tumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Larger numbers of Tregs in peripheral blood, TDLNs, and neoplasm tissues have been noted in CRC patients [ 8 , 20 , 21 ]. As has been demonstrated, most of the tumor-resident Tregs are thymus derived, while about half of the Treg population in nontumoral areas of the colon is induced Tregs (iTregs) which are generated in the periphery [ 22 ]. However, the role of Tregs in CRC is debatable [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are either considered dysfunctional Treg cells, or activated effector T cells with transient expression of Foxp3 [77,80]. It has been suggested that CD4 + CD25 − FoxP3 + cells may be a heterogeneous population with effector or suppressive phenotype [81].…”
Section: Monofunctional T Cells (T Cells Produce Only One Cytokine)mentioning
confidence: 99%